2019
DOI: 10.1002/ece3.5542
|View full text |Cite|
|
Sign up to set email alerts
|

The complete mitochondrial genomes of two vent squat lobsters, Munidopsis lauensis and M. verrilli: Novel gene arrangements and phylogenetic implications

Abstract: Hydrothermal vents are considered as one of the most extremely harsh environments on the Earth. In this study, the complete mitogenomes of hydrothermal vent squat lobsters, Munidopsis lauensis and M. verrilli, were determined through Illumina sequencing and compared with other available mitogenomes of anomurans. The mitogenomes of M. lauensis (17,483 bp) and M. verrilli (17,636 bp) are the largest among all Anomura mitogenomes, while the A+T contents of M. lauensis (62.40%) and M. verrilli (63.99%) are the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 99 publications
1
8
0
Order By: Relevance
“…The mitochondrial genomes (mitogenomes) provide rich phylogenetic information not only in the sequences, but also in the genomic rearrangements (Boore, 1999;Sun et al, 2003;Tan et al, 2017). In the Decapoda, novel mitochondrial gene orders have been reported across a range of lineages, such as brachyurans (Zhang et al, 2020;Wang et al, 2021), anomurans (Sun et al, 2019;Gong et al, 2020), and caridean shrimps (Ye et al, 2021). By analyzing 246 decapod mitogenomes, Tan et al (2019) found that a large number of mitochondrial gene orders in decapods deviated from the ancestral arthropod ground pattern and unevenly distributed among infraorders, but there was limited evidence for correlations between gene rearrangement events and species ecology or lineage-specific nucleotide substitution rates.…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial genomes (mitogenomes) provide rich phylogenetic information not only in the sequences, but also in the genomic rearrangements (Boore, 1999;Sun et al, 2003;Tan et al, 2017). In the Decapoda, novel mitochondrial gene orders have been reported across a range of lineages, such as brachyurans (Zhang et al, 2020;Wang et al, 2021), anomurans (Sun et al, 2019;Gong et al, 2020), and caridean shrimps (Ye et al, 2021). By analyzing 246 decapod mitogenomes, Tan et al (2019) found that a large number of mitochondrial gene orders in decapods deviated from the ancestral arthropod ground pattern and unevenly distributed among infraorders, but there was limited evidence for correlations between gene rearrangement events and species ecology or lineage-specific nucleotide substitution rates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also found positive selection in ATP genes for many deep-sea animals, such as sea anemone [ 77 ] and shrimp [ 25 ], indicating potential adaptation to marine extreme environments. ATP dehydrogenase not only is the last enzyme complex in the respiratory chain, but also is a part of the regulatory system of complex V [ 78 ]. The atp6 subunit plays an important role in the assembly of F0 proton in ATP synthase, which suggest that mutation in the atp6 gene may affect the production of ATP [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our conclusion is in accordance with previous workers, who suggested that gene rearrangements, to some extent, contain phylogenetic information. For example, Shao et al 64 compared the mitochondrial gene arrangements of 12 anomurans and found that Munidopsis lauensis and M. verrilli are most closely related to Shinkaia crosnieri . Based on the comparative analysis of mitochondrial gene arrangement within Coleoidea, Akasaki et al 65 concluded that order Octopoda might be the most ancestral among this subclass Coleoidea.…”
Section: Discussionmentioning
confidence: 99%